1998
DOI: 10.1073/pnas.95.6.2944
|View full text |Cite
|
Sign up to set email alerts
|

A large and distinct rotation of the myosin light chain domain occurs upon muscle contraction

Abstract: For more than 30 years, the fundamental goal in molecular motility has been to resolve force-generating motor protein structural changes. Although low-resolution structural studies have provided evidence for force-generating myosin rotations upon muscle activation, these studies did not resolve structural states of myosin in contracting muscle. Using electron paramagnetic resonance, we observed two distinct orientations of a spin label attached specifically to a single site on the light chain domain of myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
203
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(239 citation statements)
references
References 43 publications
(48 reference statements)
25
203
4
Order By: Relevance
“…Relatively early work showed that mollusc myosin has the typical two headed structure of other myosins (Elliott et al, 1976), that in the rest state ADP binds to both heads (Marston and Lehman, 1974;Shibata-Sekiya, 1982), that ATP binding alters tryptophan fluorescence (Kondo et al, 1979;, that a tryptophan present in the skeletal ATP binding site is replaced in scallop by an arginine (Kondo et al, 1979;Kerwin and Yount, 1992), and identified portions of the heavy chain and myosin head required for ATPase activity (Szentkiralyi, 1987) and actin binding (Castellani et al, 1987). Electron paramagnetic resonance showed that force generation (but not ATP hydrolysis) is associated with light chain rotation (Baker et al, 1998;Roopnarine et al, 1998;Cooke, 1998;BrustMascher et al, 1999;LaConte et al, 2003), and measurement of luminescence resonance energy transfer between the regulatory light chains showed that the light chains of both heads rotate together to act as a coordinated lever arm (Lidke and Thomas, 2002).…”
Section: 32mentioning
confidence: 99%
“…Relatively early work showed that mollusc myosin has the typical two headed structure of other myosins (Elliott et al, 1976), that in the rest state ADP binds to both heads (Marston and Lehman, 1974;Shibata-Sekiya, 1982), that ATP binding alters tryptophan fluorescence (Kondo et al, 1979;, that a tryptophan present in the skeletal ATP binding site is replaced in scallop by an arginine (Kondo et al, 1979;Kerwin and Yount, 1992), and identified portions of the heavy chain and myosin head required for ATPase activity (Szentkiralyi, 1987) and actin binding (Castellani et al, 1987). Electron paramagnetic resonance showed that force generation (but not ATP hydrolysis) is associated with light chain rotation (Baker et al, 1998;Roopnarine et al, 1998;Cooke, 1998;BrustMascher et al, 1999;LaConte et al, 2003), and measurement of luminescence resonance energy transfer between the regulatory light chains showed that the light chains of both heads rotate together to act as a coordinated lever arm (Lidke and Thomas, 2002).…”
Section: 32mentioning
confidence: 99%
“…16). Electron paramagnetic resonance studies, utilizing a probe on the regulatory light chain have shown a 30°rotation of this region (17), suggesting that the lever arm region rotates relative to the catalytic domain during muscle contraction. In addition, fluorescence studies utilizing a fluorescent probe at the regulatory light chain demonstrated rotation of the lever arm in contracting muscle fibers (15).…”
mentioning
confidence: 99%
“…Force generation by myosin is associated with the transition from a state of weak actin binding, characterized by dynamic disorder, to an ordered, strong actin-binding state (1). The weak-to-strong transition is associated with large-scale rotation of the light-chain domain (LCD) 4 relative to the catalytic domain (CD) (1)(2)(3)(4)(5). The rotation of the LCD, acting as a lever arm, displaces the associated actin filament, generating movement.…”
mentioning
confidence: 99%